Melatonin prevents hypochlorous acid‐mediated cyanocobalamin destruction and cyanogen chloride generation. Issue 3 (9th January 2018) - Jeelani, Roohi; Maitra, Dhiman; Chatzicharalampous, Charalampos; Najeemuddin, Syed; Morris, Robert T.; Abu‐Soud, Husam M.
Abstract: Hypochlorous acid (HOCl) is a potent cytotoxic oxidant generated by the enzyme myeloperoxidase (MPO) in the presence of hydrogen peroxide (H2 O2 ) and chloride (Cl − ). Elevated levels of HOCl play an important role in various pathological conditions through oxidative modification of several biomolecules. Recently, we have highlighted the ability of HOCl to mediate the destruction of the metal‐ion derivatives of tetrapyrrole macrocyclic rings such as hemoproteins and vitamin B12 (VB12 ) derivatives. Destruction of cyanocobalamin, a common pharmacological form of VB12 mediated by HOCl, results in the generation of toxic molecular products such as chlorinated derivatives, corrin ring cleavage products, the toxic blood agents cyanide (CN − ) and cyanogen chloride (CNCl), and redox‐active free cobalt. Here, we show that melatonin prevents HOCl‐mediated cyanocobalamin destruction, using a combination of UV‐Vis spectrophotometry, high‐performance liquid chromatography analysis, and colorimetric CNCl assay. Identification of several melatonin oxidation products suggests that the protective role of melatonin against HOCl‐mediated cyanocobalamin destruction and subsequent CNCl generation is at the expense of melatonin oxidation. Collectively, this work highlights that, in addition to acting as an antioxidant and as a MPO inhibitor, melatonin can also prevent VB12 deficiency in inflammatory conditions such as cardiovascular and neurodegenerative diseases, among many others.